Wetting of nanophases: Nanobubbles, nanodroplets and micropancakes on hydrophobic surfaces - An, Hongjie; Liu, Guangming; Craig, Vincent S.J. (Advances in colloid and interface science, 2015)
The observation by Atomic Force Microscopy of a range of nanophases on hydrophobic surfaces poses some challenging questions, not only related to the stability of these objects but also regarding their wetting properties. Spherical capped nanobubbles are observed to exhibit contact angles that far exceed the macroscopic contact angle measured for the same materials, whereas nanodroplets exhibit contact angles that are much the same as the macroscopic contact angle. Micropancakes are reported to consist of gas, in which case their wetting properties are mysterious. They should only be stable when the van der Waals forces act to thicken the film whereas for a gas, the van der Waals forces will always act to thin the film. Here we examine the available evidence and contribute some additional experiments in order to review our understanding of the wetting properties of these nanophases. We demonstrate that if in fact micropancakes consist of a contaminant their wetting properties can be explained, though the very high contact angles of nanobubbles remain unexplained. [Display omitted] •The anomalous contact angle of nanobubbles is examined.•The unusual wetting properties of micropancakes are explored.•Contamination from plastic syringes leads to micropancake structures.•Nanobubbles are observed in Dimethylsulfoxide (DMSO).•Contamination produces micropancake structures in DMSO.